An insight into the world of sports dentistry - Kumar, G.; Dash, P.; Jha, K.; Singh, A. (The Journal of Sports Medicine and Physical Fitness, 2021)
Dental trauma in the field of sports is the major linking channel between sports and dentistry. Sports dentistry is the branch of sports medicine that deals with the prevention of oral or facial athletic injuries, oral diseases and manifestations. Sports dentistry is also related to mild traumatic brain injuries during games and erosive lesions due to continuous intake of highly acidic sports and energy drinks. Stress among sportsperson has also been depicted to impact their athletic performance leading athletes to the intake of drugs. Smokeless tobacco consumption and sponsorship is also found among athletes. Therefore, it is emphasized the need for a "team dentist," initiating from high schools to professional teams. The sports or "team dentist" assists athletes in the effective prevention, treatment, and diagnosis of various types of oral injuries. Sport-related orofacial injuries can be prevented by wearing primary protective devices such as properly fitting helmets, face masks and/or mouth guards. They can also enlighten athletes about the benefits of practicing yoga, as it reduces stress and improves performance. Hence, the dentist can perform an imperative role in informing parents, athletes, coaches and patients about the importance of preventing orofacial injuries in sports.